Innovation in the Italian sector of vending machines: Between growth and search for sustainability - Roberto Henke; Roberta Sardone (Italian Review of Agricultural Economics (REA), 2020)
Changes in lifestyles involve many aspects of food consumption widely analysed in literature, while the development of specific distribution forms, such as the vending machines, are less known and still perceived unsuitable to respond to the segmentation of demand. This sector is recording impressive growth rates. Italy is the country in Europe with the highest number of machines, as well as being leader in the production of machines and in the development of management services. This growth is not extraneous to the search for greater qualification of the foodstuff supply. The most recent data show numerous experiences aimed at introducing a more accurate selection of products supplied. Nevertheless, the agricultural sector doesn't seem to be adequately involved in the vending machines supply chain, except for some limited experiences. The objective of the paper is to analyse the most significant initiatives to assess whether they could contribute to the reinforcement of the role of agriculture and to the definition of new criteria within the selection procedures for vending services.
Keywords: Q18; I12; 330; vending machines; food consumption behaviour; public food procurement